Accounting for Wealth Concentration in the US - Barıș Kaymak; David Leung; Markus Poschke (Institute of Labor Economics (IZA), 2020)
The recent literature has argued for high concentration of earnings, differences in rates of return on assets and bequests as potential determinants of the high level of wealth concentration in the US. Analyzing the joint distribution of earnings, capital income and net worth, we find evidence for excess returns on investment among the highest income groups. Nonetheless, concentration of labor earnings is the primary source of wealth concentration in the US. This finding reflects the high correlation between earnings and wealth in the data, as well as the fact that earnings are a major source of income for top income and wealth groups.
Keywords: D31; H24; O54; 330; wealth inequality; rate of return heterogeneity; income risk; bequests